Comparison of Forced Expiratory Flow (FEF) 25-75% between Post-COVID-19 Patients with Different Severity at Universitas Gadjah Mada Academic Hospital - Khidir, Muhammad; Siswanto, Siswanto; Rasena, Henda Ageng; Iqbal, Roihan Mohamad; Sabirin, Rahmaningsih Mara; Wibowo, Rakhmat Ari; Rasyid, Sani Hadiyan (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Shortness of breath is the most distressing long COVID-19 symptom associated with the decline of small airway function, as shown by a decrease in forced expiratory flow (FEF) 25-75% value in the spirometry test. This study aimed to compare FEF 25-75% values as a predictor of small airway disease between mild-moderate and severe-critical long COVID-19 patients. Methods: This study used a prospective cohort design that included 24 post-hospitalized COVID-19 patients who came to the long COVID-19 clinic at Universitas Gadjah Mada Academic Hospital (UGM AH), Yogyakarta. The subjects were divided into mild-moderate and severe-critical groups based on the World Health Organization (WHO) classification. The subjects were tested for spirometry three months after the onset of COVID-19 symptoms. The comparison of both severity groups used the percent prediction of FEF 25-75% spirometry results. The value was interpreted as abnormal if the predicted FEF 25-75% value was below 65%. Results: There were three (25%) and two (16.67%) subjects with FEF 25-75% predicted below normal values in the mild-moderate and severe-critical groups consecutively, which showed a decline in small airway function. This study showed no statistically significant differences (p-value = 0.882) between the means of FEF 25-75% predicted values of the two groups. Conclusion: A small proportion of post-COVID-19 syndrome patients had small airway disease, and there were no statistical differences in small airway function between the groups.